Perlindungan Hukum Bagi Korban Kekerasan Seksual di Perguruan Tinggi - Ayu Safitri; Abd. Asis; Nur Azisa (Al-Mizan (e-Journal), 2023)
This study aims to analyse the form of legal protection for victims of sexual violence in higher education and the factors that become obstacles in providing legal protection for victims of sexual violence in higher education. This research is an empirical research type with data collection techniques through interviews and literature studies. The data obtained is analysed qualitatively and presented descriptively. The results of the study indicate that the form of legal protection for victims of sexual violence that occurs in Higher Education is provided by providing victims' rights which have been regulated in Law Number 12 of 2022; Law Number 13 of 2006; Decree of the Director General of Islamic Education Number 5494 of 2021; and Regulation of the Minister of Education, Culture, Research and Technology Number 30 of 2021. The factors that influence the provision of legal protection for victims of sexual violence, namely legal factors, there are still articles that are still abstract, law enforcement factors that are still ineffective in carrying out their duties, and facilities or facilities have not been fulfilled properly, both offices and funding.